Project-Based Learning With TikTok: A Digital Strategy for OHS Regulatory Training - Danny Javier Lluguay-Quispillo; Diana E. Guaya (Emerging Science Journal, 2025)
This study examines the pedagogical integration of TikTok within a Project-Based Learning (PBL) framework to enhance the teaching and internalization of Occupational Health and Safety (OHS) regulations in higher education, specifically Executive Decree 255. The primary aim was to evaluate the effectiveness of student-created TikTok videos in fostering active learning, regulatory comprehension, and the development of key academic and professional competencies. Seventy-three undergraduate students from the Practicum III course in the OHS program at Universidad Técnica Particular de Loja participated in the initiative. The structured methodology comprised five phases: topic assignment, digital training, guided video production, public dissemination, and multidimensional evaluation. Student outcomes were assessed through rubric-based evaluation, TikTok engagement analytics, and a validated satisfaction questionnaire addressing eight pedagogical constructs (Cronbach’s α=0.989; KMO=0.934). Results indicate enhanced conceptual understanding, increased motivation, and the strengthening of transversal competencies such as digital communication and learner autonomy. The novelty of this approach lies in the purposeful use of a widely adopted social media platform as both a pedagogical tool and a dissemination medium, offering a replicable model for other STEM disciplines that require the translation of complex regulatory or technical content into engaging and accessible formats.